Validation of Sterile Water for Injection In Pharmaceutical Industry and Othersterile Facility - Choudhary, Neetu; Patil, Bhagyashri; Choukse, Raju; Varma, Ajit Kumar; Bairagee, Deepika; Kulkarni, Sweta (Asian Journal of Pharmaceutical Research and Development, 2019)
Sterile facilities for all pharmaceutical product specially to parentral preparation, is a must important back bone of sterile formulation andor pharmaceutical dosage form. There is most important to sterile of the areas where the formulation process proceed from initial to final stage. The sterile injectable products are very critical and sensitive products as they are administered directly into blood circulation. These products are designed such that it should be free from micro-organisms, pyrogens and unacceptable particulate matter. Any failure in quality and purity of these products may directly affect the safety of patient being treated. FDA, WHO, ISO and Good Manufacturing Practiceshas established the guides to the development of sterile pharmaceutical preparation facilities for health care establishments.This report covers all summaries that the three batches of Methylcobalamine injection 2 ml have been validated with the support of process validation protocol.